Unannounced phone-based pill counts for monitoring antiretroviral medication adherence in South Africa - Seth Kalichman; Ellen Banas; Bruno Shkembi; Moira Kalichman; Catherine Mathews (HIV Research & Clinical Practice)
Background Unannounced phone-based pill counts (UPC) are an objective measure of medication adherence that may be used in resource limited settings. The current study reports the feasibility and validity of UPC for monitoring antiretroviral therapy (ART) adherence among people living with HIV in South Africa. People living with HIV (N = 434) in an economically impoverished township and receiving ART for at least 3-months completed: two UPC in a one-month period; measures of clinic and medication experiences; and provided blood samples for HIV viral load and CD4 testing. Analyses compared two methods for managing values of over-dosing (> 100%), specifically censoring values to 100% (> 100% = 100%) vs. subtracting over-dosing from two months of perfect adherence (200% - > 100% value). Results Findings showed that two UPC calls were successfully completed with 91% of participants in a one-month period. The average number of call attempts needed to reach participants was 2.4. Results showed that lower UPC adherence was significantly associated with male gender, alcohol use, higher HIV viral loads, lower CD4 cell counts, running out of ART, and intentionally not taking ART. Comparisons of methods for adjusting over-dosing found subtraction yielding a better representation of the data than censoring. Conclusions UPC were demonstrated feasible and valid with patients receiving ART in a resource limited setting and offers a viable method for objectively measuring ART adherence in these settings.